Classical studies in Tucumán (Circe de clásicos y modernos, 2018)
Since the beginning of the 20th century, classical culture became the focus of attention of the cultural life in the province of Tucuman, a fact well documented in the chroni-cles of the time. Writers, poets and artists of the Greco-Latin tradition were hosted by many governors who were aware of their valuable contribution to the field and their relevance to the province. This article refers to the impact classical studies have had in the fields of philosophy, literature and art at the National University of Tucumán to date as attempt to acknowledge the significance of this inherited classical tradition.
Keywords: Classical studies; National University of Tucumán; Classical art